2009
DOI: 10.1073/pnas.0806661106
|View full text |Cite
|
Sign up to set email alerts
|

Invariant phase structure of olivo-cerebellar oscillations and its putative role in temporal pattern generation

Abstract: Complex movements require accurate temporal coordination between their components. The temporal acuity of such coordination has been attributed to an internal clock signal provided by inferior olivary oscillations. However, a clock signal can produce only time intervals that are multiples of the cycle duration. Because olivary oscillations are in the range of 5-10 Hz, they can support intervals of Ϸ100 -200 ms, significantly longer than intervals suggested by behavioral studies. Here, we provide evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 45 publications
(60 reference statements)
1
49
0
Order By: Relevance
“…Several solutions have been proposed on how the population complex spike activity can provide a much finer temporal resolution than individual Purkinje cells. One solution relies on the observation of non-zero phase lags among the complex spike discharge of Purkinje cells in different regions of the cerebellar cortex to generate time intervals shorter than the normal periodicity of inferior olivary neurons [102]. However, support for this concept has only been obtained after administration of harmaline.…”
Section: Potential Issues With Error Encoding By Complex Spikesmentioning
confidence: 99%
“…Several solutions have been proposed on how the population complex spike activity can provide a much finer temporal resolution than individual Purkinje cells. One solution relies on the observation of non-zero phase lags among the complex spike discharge of Purkinje cells in different regions of the cerebellar cortex to generate time intervals shorter than the normal periodicity of inferior olivary neurons [102]. However, support for this concept has only been obtained after administration of harmaline.…”
Section: Potential Issues With Error Encoding By Complex Spikesmentioning
confidence: 99%
“…IO rhythmicity could definitely contribute to the organization of network activity in the cerebellar cortex (Jacobson et al, 2008; Llinás, 2009). Recent models suggest that this network may be capable of influencing PCs at a much finer temporal resolution than 10 Hz (Jacobson et al, 2008, 2009). Their model posits that GABAergic input from the DCN, which decouples IO cells by acting on gap junctions (Lang et al, 1996), would set cells out of phase from each other.…”
Section: Different Types Of Oscillations In the Cerebellar Cortexmentioning
confidence: 99%
“…In another case (Devor and Yarom 2002b), patches of spontaneous or stimulus-evoked STOs were observed within which the oscillations were not spatially stationary but instead propagated rapidly in a wave-like manner throughout the local network resulting in the establishment of phase differences between cells. In agreement with this, in vivo multi-electrode array recordings of Purkinje cell complex spike activity in awake rats (Jacobson et al 2009) suggest that, rather than being exactly in phase, stable phase differences can exist between neurons which oscillate at the same frequency. A networked compartmental model of olivary neurons (Schweighofer et al 1999) demonstrated that these phase differences can be achieved by variations in coupling strength between the oscillating neurons.…”
Section: Gap Junctions and Synchronymentioning
confidence: 80%
“…A recent study suggests that even asynchronous climbing fibers fire at fixed time intervals with respect to each other (Jacobson et al 2009) which is proposed to reflect fixed phase offsets between olivary neurons oscillating at the same frequency. Synchrony results from a combination of the electrotonic coupling between IO cells (Blenkinsop and Lang 2006), the subthreshold oscillations themselves (Lang et al 1997), the branching of a single olivary axon into multiple climbing fibers (Lang et al 2006a), and shared excitatory synaptic input between neighboring olivary neurons (Kistler et al 2002).…”
Section: Rhythmicity and Synchrony In The Climbing Fiber Systemmentioning
confidence: 98%